Chapter 11 Funding the UN Support or Constraint? - Baumann, Max-Otto (Taylor & Francis, 2020)
This chapter shows that while the UN development system (UNDS) has benefited from a strong increase in resources over recent years, it suffers from the reliance on a small number of contributing countries and a disproportionate earmarking of funds. While softer forms of such tied funding can be credited with fostering coherence, efficiency, and innovation in the UN's country-level work, tightly earmarked project funding has substantial, and not yet fully recognized negative implications for the development effectiveness and multilateral functions of the UNDS. Efforts to contain the rise of earmarked funding (which is driven both by political interests of member states and the desire to financially grow UN organizations) and broaden the base of contributors, have so far been ineffective. The UN Funding Compact presents the first systemic answer that brings together member states and UN development organizations. It remains to be seen whether it can slow down harmful funding practices and equip the UNDS with the resources required so that it can act as a catalyst for implementing the 2030 Agenda.